A KOLABORASI MULTIDISIPLIN UNTUK MENDUKUNG KESEHATAN OTAK IBU HAMIL: KOLABORASI MULTIDISIPLIN UNTUK MENDUKUNG KESEHATAN OTAK IBU HAMIL - Pratiwi, Niken; Hipni, Rubiati; Hutagaol, Rutmauli (UPPM Poltekkes Kemenkes Banjarmasin, 2025)
In pregnant women, maintaining brain health is very important. Improving the health status of pregnant women can be done through multidisciplinary collaboration to support the brain health of pregnant women by involving various integrated approaches. This community service aims to optimize the brain health of pregnant women by implementing an effective education program. This community service is carried out by providing counseling and educational interventions carried out in an integrated manner by various health professions of the multidisciplinary team to pregnant women in the PKM Sungai Malang area in increasing the knowledge of pregnant women about brain health in pregnant women and fetuses. The results of this community service Before being given counseling, most pregnant women, as many as 24 people (85.71%) had poor knowledge, but after counseling, most of them, as many as 22 people (78.57%) showed an increase in knowledge to good. The conclusion is that multidisciplinary counseling is effective in increasing the knowledge and understanding of pregnant women regarding the importance of stimulation and nutrition for fetal brain development. This approach is expected to reduce the risk of pregnancy complications and improve the overall well-being of the mother and fetus